Software design process ontology development - Wongthongtham, Pornpit; Chang, Elizabeth; Dillon, Tharam S. (Springer-Verlag, 2006)
Software design process has been followed and widely used to describe logical organisation of software using different types of models. However, when it comes to remote communication over software design, it is prone to miscommunication, misunderstanding or misinterpretation especially with ambiguous terms or people having different backgrounds and knowledge of the software design process. This motivates the use of unified knowledge representation of software design process i.e. software design process ontology for communications and coordination. The knowledge representation introduced here in the form of software design process ontology is based on a formal description of the software design process using the web ontology language OWL. Software design process knowledge is defined or captured in a formal and machine processable fashion. The software design process knowledge is then open and facilitates the sharing of software design among software engineers. We discuss software design process ontology development in this paper.